Implementasi Tujuan Instruksional Umum di Era Pandemi Covid-19 di SDN Periuk Jaya Permai Tangerang - Ismawanti, Agnes; Putri, Disa Cahaya; Azzahra, Fernita Dwi (Lembaga Yasin AlSys, 2022)
This study aims to find out how teachers provide and transfer knowledge in the era of the Covid-19 pandemic at SDN Periuk Jaya Permai Tangerang. Since the Covid-19 pandemic, all schools in Tangerang, including SDN Periuk Jaya Permai, Tangerang. The type of this research is observation, interview guide and researcher as instrument and key. The source of the data for this research is the results of interviews with teachers at the SDN. This study aims to determine the problems experienced by teachers and students in the learning process in the Covid-19 pandemic era. The conclusion obtained from this research is that there are still obstacles to teachers and students in implementing and carrying out instructional objectives appropriately.